The Role of Extra-Campus Student Organizations in Improving Religious Moderation (Case Study of Cipayung Student Organization Group Plus Kendari City) - Asman, Asman; Mualimmah, Mualimmah (Fenomena, 2023)
The role of students in religious moderation is significant to note. This is because student organizations have members from various religious ideologies, which have the potential to clash with each other. This is because many students need help understanding the concept of religious moderation that occurs. This research aims to analyze and discover the role of extra-campus student organizations in increasing religious moderation among university students, especially in the Cipayung Plus student group in Kendari City. The Cipayung Plus Kendari student group is a campus organization of various religions and religious ideologies. Islamic-based organizational groups are represented by the Muhammadiyah Student Association (IMM), the Islamic Student Association (HMI), the Indonesian Islamic Student Movement (PMII), and the Indonesian Muslim Student Action Union (KAMMI). Christian student organizations, namely the Republic of Indonesia Catholic Student Association (PMKRI) and the Indonesian Christian Student Movement (GMKI). ORGANIZATIONS with nationalist backgrounds, such as the Indonesian National Student Movement (GMNI) and the National Democratic Student League (LMND). The method in this study is descriptive qualitative. Observation, interviews, and documentation are used to do power collection. The data is processed using the Miles model and Huberman theory analysis: data collection, data reduction, data presentation, verification, and conclusion. The results showed that the Cipayung plus Kendari City student organization group significantly increased religious moderation among students. This is demonstrated by tolerance values, egalitarian values ​​(equality), and unity between organizations with different beliefs. The Cipayung Plus organization, Kendari City, has carried out this role.